The self-relevance system?. Issue 1 (1st October 2016) - Conway, Martin A.; Pothos, Emmanuel M.; Turk, David J.
Abstract: We suggest that the Self Attention Network (SAN) maybe part of a larger self-regulatory system, which we term the Self-Relevance System (SRS) of which the "core" or default network is a major part. It is within the core network that memories are generated and the future imagined. Such memories and imaginings are the basis of preoccupations. Within the SRS then preoccupations drive the emergence of attentional biases (ABs). ABs in turn are modulated by the SAN activating and inhibiting circuits that shape behavior. We consider briefly how this might function in dysfunctional appetitive behaviors, e.g., substance abuse.